Development of electrochemical methods of neutralization of nitric oxides, using lump electrodes with developed surface in aqueous solutions - Baeshova, A. K.; Kondaurov, R. K.; Baeshov, A. B. (International Journal of Biology and Chemistry, 2012)
Nitrogen oxides were electrochemically oxidized into nitrates with the goal of decreasing pollution of environment. Results showed that increasing of concentration of electrolyte and increasing the volume of passing gas mixture increases current output. But increasing the current density decreases current output. Results were obtained by using Photo electric colorimeter.